Aspects of nucleic acid metabolism during nutritional deficiency in Escherchia coli - Smith, B (1964)
This thesis concerns an investigation of the effects of thymine deficiency in thymineless mytants of Escherichia coli. Evidence was available which implicated damage to the DNA of the cell as the cause of the loss of viability (thymineless death) which accompanies thymine deficiency. DNA has been extracted from bacteria before and after thymineless death and examined for chemical and physical differences. There was evidence that the DNA extracted after thymineless death was labile to alkali shince it could not be reprecipitated with acid after the accompanying RNA had been destroyed by alkali according to the method of Schmidy and Thannhauser. It had also been observed that incubation of the acid-insoluble residue from bacteria after thymineless death in N alkali for 16 hours at 37 degrees resulted in an apparent decrease in material which reacted in the diphenylamine assay for DNA. It has been shown that the inability to reprecipitate the DNA is not a function of the DNA itself since if herring sperm DNA is added to the alkaline incubation mixture it too cannot be reprecipitated. The apparent decrease in diphenylamine-reacting material was shown to be due to the production during thymine deficiency of some material which when treated with alkali produced an inhibitor of the diphenylamine reaction. It has further been shown that incubation in alkali reduces the viscosity of DNA extracted after thymineless death by about the same amount as that of DNA extracted before thymineless death. [please see PDF to read the rest of the abstract]